Grounded Theory disertai Model Triple-C dalam Upaya Meminimalisir Prokrastinasi Akademik Belajar Fisika Berbasis Livezopadizdo - Hartini Dewi (Ideguru: Jurnal Karya Ilmiah Guru, 2022)
Procrastination in learning physics by students who are seen from the point of view of their failure in working on, completing, and collecting answers to physics which is the background of this research. The first objective of this study is to reconstruct the pattern of learning difficulties in understanding the process of student behavior in order to minimize academic procrastination. Second, to find out the percentage of implementation of the Triple-C model in minimizing physics academic procrastination. Third, knowing the percentage of completeness in learning physics with the Triple-C model based on Livezopadizdo. The Triple-C model with the following phases Controversial Group, Exploring, Communication Deep Dialog, and Clarification Concept. The data analysis technique uses the Grounded Theory method. The conclusions obtained from this study are: first, the construction of patterns of learning difficulties in understanding the process of student behavior in order to minimize academic procrastination in the pandemic era with teaching and learning activities in online and offline conditions. Second, the average percentage of the implementation of the Triple-C model in minimizing physics academic procrastination is 92.2%. Third, the percentage of completeness in learning physics in the application of Livezopadizdo accompanied by the Triple-C cycle model is 100%.